Players in pigtails - Corey, Shana; Gibbon, Rebecca (New York Scholastic Press, 2003)
Katie Casey, a fictional character, helps start the All-American Girls Professional Baseball League, which gave women the opportunity to play professional baseball while America was involved in World War II.
Keywords: All-American Girls Professional Baseball League -- History -- Juvenile fiction; All-American Girls Professional Baseball League -- History -- Fiction; Baseball -- History -- Fiction; Sex role -- Fiction